2004
DOI: 10.4049/jimmunol.173.4.2435
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Signaling in Inflammatory Leukocytes Is Dispensable for 17β-Estradiol-Mediated Inhibition of Experimental Autoimmune Encephalomyelitis

Abstract: Estrogen treatment has been shown to exert a protective effect on experimental autoimmune encephalomyelitis (EAE), and is under clinical trial for multiple sclerosis. Although it is commonly assumed that estrogens exert their effect by modulating immune functions, we show in this study that 17β-estradiol (E2) treatment can inhibit mouse EAE without affecting autoantigen-specific T cell responsiveness and type 1 cytokine production. Using mutant mice in which estrogen receptor α (ERα) has been unambiguously ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 57 publications
8
72
2
2
Order By: Relevance
“…These results are consistent with the findings that pregnancy as well as estrogen treatment during EAE induces a population of CD45 dim VLA-4 + regulatory cells that appear to be non-T cells but confer protection from EAE (Matejuk et al 2004). Additional studies using bone marrow chimeras further support these observations and provide evidence that E2 may act on nonhematopoietic cells such as endothelial cells, or on resident cells of the CNS (for example, microglia) to prevent disease (Garidou et al 2004). Modulation of cells such as these by E2 may in turn suppress the activation and/or function of T cells.…”
Section: Discussionsupporting
confidence: 79%
“…These results are consistent with the findings that pregnancy as well as estrogen treatment during EAE induces a population of CD45 dim VLA-4 + regulatory cells that appear to be non-T cells but confer protection from EAE (Matejuk et al 2004). Additional studies using bone marrow chimeras further support these observations and provide evidence that E2 may act on nonhematopoietic cells such as endothelial cells, or on resident cells of the CNS (for example, microglia) to prevent disease (Garidou et al 2004). Modulation of cells such as these by E2 may in turn suppress the activation and/or function of T cells.…”
Section: Discussionsupporting
confidence: 79%
“…(E2) on EAE induction in ER-mutant mice clearly showed that this protective effect of E2 was mediated through ERa but not ERb [6][7][8]. Altogether, these studies support a protective role of estrogens on EAE that could explain the protective effect of pregnancy on MS [9].…”
supporting
confidence: 63%
“…Estrogens are able to shift the T-cell population towards a Th2 phenotype, an activity also confirmed in pilot clinical studies ( [47,83,211,214]) and to influence a subpopulation of Th cells, named T-regulatory cells ( [184,226]). On the other hand, microglia and endothelial cells have probably a more significant role in estrogen action; using irradiation bone marrow chimeras it has been recently shown that the effect of estradiol on clinical EAE and CNS inflammation was not dependent on ERa expression in the peripheral immune system but was conferred by ERa expression on CNS resident cells, namely endothelial and microglial cells ( [80,185]). It is thus important to fill the gap in the characterization of estrogen signalling in these resident brain cells and in assessing its relevance in estrogen-mediated neuroprotective activity in EAE.…”
Section: Estrogens and Multiple Sclerosismentioning
confidence: 99%
“…Through the use of the estrogen receptor antagonist ICI 182780 we and others initially ascribed hormone action in microglia to the activation of endogenous ERs, since this molecule was able to block the effect of estradiol ( [24,25,141,241]). Using ER-null mice several reports described the selective involvement of ERa in the anti-inflammatory and neuroprotective activity of estradiol against neuroinflammatory and vascular pathologies of the brain ( [62,80,185,242]). Despite the fact that ERb has been shown to be expressed widely in the CNS in adult mice ( [161,167]), it appears that this receptor isoform is not involved in mediating the protective effect of estrogens in neuroinflammatory diseases.…”
Section: The Mechanism Of Estrogen Action In Neuroinflammationmentioning
confidence: 99%